Imagination as poetics of cognition (ENTHYMEMA, 2013)
AbstractOur work bases on the hypothesis of an existing interconnection between the symbolic and the metaphoric elements of the text responding to a series of mind patterns compressing perception and experience through the emerging process of conceptual blending triggering the semantic process during the creative act of poiesis. This enquiry focuses on the use of a peculiar rhetorical figure in an exemplar literary text of the famous German poet Goethe. We will try to point out the allegorical function of the scene dedicated to the «Mothers’ Kingdom», in his Faust II as a powerful poetical meta-reflection on imagination, cognition and poetics itself.
Keywords: Imagination; hermeneutics; cognition; embodiment; Faust